2005
DOI: 10.1038/sj.onc.1208572
|View full text |Cite
|
Sign up to set email alerts
|

A germ line mutation that delays prostate cancer progression and prolongs survival in a murine prostate cancer model

Abstract: Circulating insulin-like growth factor-I (IGF-I) levels have been shown to be related to risk of prostate cancer in epidemiologic studies. While specific genetic loci responsible for interindividual variation in circulating IGF-I levels in normal men have not been identified, candidate genes include those involved in the growth hormone (GH)-IGF-I axis such as the hypothalamic factors GH releasing hormone (GHRH) and somatostatin and their receptors. To investigate the role of the GH-IGF-I axis on in vivo prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 37 publications
0
43
1
Order By: Relevance
“…This is of particular interest since haploinsufficiency of PTEN also promotes progression of prostate cancer in this model (Kwabi-Addo et al, 2001) and serum IGFBP-2 levels may portend PTEN status and PI3K Akt pathway activation in cancer patients (Mehrian-Shai et al, 2007). TRAMP mice carrying the lit germ-line mutation that inactivates the GHRH receptor (GHRH-R) also showed delayed prostate cancer progression and prolonged survival owing to reduced circulating levels of both GH and IGF-1 (Majeed et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…This is of particular interest since haploinsufficiency of PTEN also promotes progression of prostate cancer in this model (Kwabi-Addo et al, 2001) and serum IGFBP-2 levels may portend PTEN status and PI3K Akt pathway activation in cancer patients (Mehrian-Shai et al, 2007). TRAMP mice carrying the lit germ-line mutation that inactivates the GHRH receptor (GHRH-R) also showed delayed prostate cancer progression and prolonged survival owing to reduced circulating levels of both GH and IGF-1 (Majeed et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies in the transgenic adenocarcinoma of the mouse prostate model have suggested that in addition to low levels of circulating IGF1, low GH levels may also be needed to reduce prostate cancer progression (Majeed et al 2005, Anzo et al 2008. In vitro studies suggest that IGF1 and androgens may interact in prostate cancer cells (Culig et al 1994, Pandini et al 2005, and in humans, in epidemiological studies, a high serum IGF1 level is a risk factor for the development of prostate cancer (Mantzoros et al 1997, Chan et al 1998, Wolk et al 1998.…”
Section: Control Mice Li-igf1mentioning
confidence: 99%
“…The observation further suggested FGF2 as a target for chemoprevention of PCA. Similarly, the roles of ERKs, EGFR, NF-κB, clusterin, cyclins, insulin-like growth factor-I (IGF-I), DNMTs and other molecular pathways in the TRAMP carcinogenesis have also been reported by different groups [24][25][26][27][28][29][30].…”
Section: Molecular Changes In Prostate Carcinogenesis In Tramp Modelmentioning
confidence: 99%